DAMPAK KEBIJAKAN LARANGAN PEMBAKARAN LAHAN TERHADAP KONDISI EKONOMI MASYARAKAT (Studi di Desa Mekar Jaya Kabupaten Pulang Pisau) (Journal Ilmu Sosial, Politik dan Pemerintahan, 2020)
The Policy of prohibition the burning of land stipulated in the Pulang Pisau District Regulation Number 05 of 2008 aims to prevent and overcome forest and land fires that burning land is one of the causes of environmental damage and can disrupt the activities of surrounding communities. This study aims to describe and analyze the Impact of the Policy on Ban on Land Burning on the Economic Condition of the Community in Mekar Jaya Village, as well as the government's efforts to overcome these problems. With this, the researcher uses Dye's (1981) theory by considering four impacts that need to be analyzed, namely the impact of the policy on the target situation or target group; impact of policies on other situations or groups other than the situation of the target group; impact of policy on current conditions and future conditions; and identity changes in the environment related to efforts to measure government activity. The results showed that after the regulation prohibited the burning of land, considering that Mekar Jaya Village was dominated by the type of agricultural work which was the main driver of the economy, while the people in the village opened the land by burning. Because there is no community that can open land, the eventually employment for farmers become narrowed. because the narrowing of work causes a reduction in people's income. Then the price of rice and vegetables because they had to arrive from outside the region. Key words: Policy Impact, Conditions Economic